2022
DOI: 10.1108/jiabr-01-2022-0022
|View full text |Cite
|
Sign up to set email alerts
|

A proposition to implement inclusive Islamic financial planning in Indonesia through bibliometric analysis

Abstract: Purpose In Indonesia, the Islamic Economics and Finance Sector is growing rapidly, but the literature on Islamic financial literacy is still minimal. This study aims to show research opportunities with the theme of Islamic financial literacy, especially inclusive Islamic financial planning through bibliometric analysis of Scopus and connected papers. Design/methodology/approach A comma separated value (CSV) file containing more than 2,000 references meta data was used for analysis on Vos Viewer in the period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
6
0
4
Order By: Relevance
“…Perilaku keuangan seorang muslim sudah seharusnya didasarkan pada kewajiban untuk mematuhi syariat Islam, baik dalam mencari sumber pendapatan maupun penegluaran (Sevriana et al, 2022). Memiliki pemahaman yang kuat tentang literasi keuangan syariah akan membantu seorang muslim untuk menghindari praktik-praktik yang tidak sesuai dengan prinsip-prinsip syariah (Dinc et al, 2021).…”
Section: Kata Kunci: Literasi Keuangan Syariah Scopus Vosviewer Anali...unclassified
“…Perilaku keuangan seorang muslim sudah seharusnya didasarkan pada kewajiban untuk mematuhi syariat Islam, baik dalam mencari sumber pendapatan maupun penegluaran (Sevriana et al, 2022). Memiliki pemahaman yang kuat tentang literasi keuangan syariah akan membantu seorang muslim untuk menghindari praktik-praktik yang tidak sesuai dengan prinsip-prinsip syariah (Dinc et al, 2021).…”
Section: Kata Kunci: Literasi Keuangan Syariah Scopus Vosviewer Anali...unclassified
“…Di Paula and Campbell (2002) found that people with high self-esteem accomplished more goals, participated in more goal-seeking activities, expressed greater satisfaction with goal success and deliberated less about unsuccessful plans than people with low self-esteem. Moreover, Islamic financial management has become more important than ever before, specifically as the banning of interest and other prohibitions within the ecosystem should encourage Muslims to be more innovative in establishing its social, financial system (Sevriana et al , 2022). The following sub-section details hypotheses development and relationships are presented in Figure 1.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Masyarakat Muslim semakin meningkat pada setiap periode sehingga mendorong adanya permintaan ekonomi dan sosial terhadap produk dan layanan yang halal sesuai syariat Islam (Hassan et al, 2018). Meskipun jumlah masyarakat Muslim 87% dari total populasi, pada kenyataannya hanya sekitar 16 yang melek keuangan Syariah didukung dengan minimnya literatur perencanaan keuangan syariah (Sevriana et al, 2022). Dengan pemilihan penggunaan keuangan syariah membuktikan mampu berkontribusi nyata dalam pertumbuhan perekonomian.…”
Section: Pendahuluanunclassified